Revolutionizing Education: Exploring the World's Most Engaging Interactive Technologies and Effective Teaching Approaches - Shermukhammadov, Shermukhammadov (Pedagogia : Jurnal Pendidikan, 2023)
The aim of this study is to explore the latest innovations and advanced foreign experiences in teaching pedagogical sciences. A qualitative research approach was employed to gather data from various sources, including academic literature, interviews with pedagogy experts, and case studies of innovative teaching practices in foreign countries. The results of this study indicate that there are several innovative teaching methods and practices that have been successfully implemented in foreign countries, such as flipped classrooms, project-based learning, and the use of technology in education. These practices have been shown to improve student engagement and achievement, as well as foster critical thinking and problem-solving skills. The implications of this study suggest that there is a need for greater collaboration and knowledge sharing between educators and institutions across borders, to promote the adoption of innovative teaching practices and enhance the quality of pedagogical education. Additionally, this study highlights the importance of continuously reviewing and updating teaching practices in response to the evolving needs and demands of the educational landscape.